2008
DOI: 10.1177/0731684408090368
|View full text |Cite
|
Sign up to set email alerts
|

Residual Strength of Stitched Laminates After Low Velocity Impact

Abstract: Tests were conducted with stitched laminates in order to calculate CAI (compression after impact) strength and TAI (tension after impact) strength for stitched laminates. Two levels of low velocity impact energy were used. All the specimens were made of two different types of lay-up sequence laminates with three different stitching directions of 08, 458, and 908. FEM model was developed using MSC/PATRAN software to predict the CAI and TAI strength of stitched laminates. PS criterion (point stress) and FD crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Delamination is a critical failure mechanism since it causes big losses of the structure's residual compressive strength after impact [9][10][11][12]. Most of the time, the largest axis of delamination damage runs in the direction of the fibres of the lower sheet [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delamination is a critical failure mechanism since it causes big losses of the structure's residual compressive strength after impact [9][10][11][12]. Most of the time, the largest axis of delamination damage runs in the direction of the fibres of the lower sheet [3].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the time, the largest axis of delamination damage runs in the direction of the fibres of the lower sheet [3]. After perforation, it has been shown that the residual tensile strength of woven laminates diminishes [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to composite CAI strength studies, less research has been performed regarding tension after impact (TAI) strength, also a very important issue in evaluation and design of composite structures. Cheng et al 21 used both numerical and experimental methods in studying TAI strength of stitched laminates. Two different types of laminate lay-up sequences with three different stitching directions of 0 o , 45 o , and 90 o were considered, with two levels of low-velocity impact energy applied to the specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with 3D braided ceramic matrix composite (CMC), 2D woven CMC laminate has the advantages of lower manufacture cost and better stiffness design and the disadvantages of weaker interlaminar strength and easier delamination. Scholars began an investigation into improving interlaminar fracture toughness of composite materials and put forward many different interlayer toughening methods, such as, interleaved film toughening [1,2] , thermoplastic-particle interlayer toughening [3,4] , stitching [5][6][7] and Z-pins [8][9][10][11][12] . Interleaved film and thermoplastic-particle interlayer toughening methods are feasible for the polymer composites, but can not be used in ceramic matrix composites.…”
Section: Introductionmentioning
confidence: 99%